Akute trauma, en Rudolf Otto se godsdiens-psigologiese teorie as middel tot heling - Endres, Annelize (HTS teologiese studies, 2009)
Acute trauma, and Rudolf Otto’s psychology of religion theory as means for healingEmpirical studies confirm that quantitative research is limited as far as the analysis, description and explanation of traumatic experiences are concerned. It is after all virtually impossible to quantify emotions. This article aims to overcome this obstacle by applying Rudolf Otto’s theory of psychology of religion, and more specifically his theory on the transformation of fear (tremens) into awe (fascinans), to pastoral care with traumatised persons. Trauma is the internal experience of an external event, and causes fear and alienation. In psychology of religion, fear pertains to alienation from God and fellow believers, whereas awe refers to the emotionally laden response to transcendence. Moving from fear to awe leads to wholeness within a person, and peace in human interactions. Wholeness overcomes alienation, and facilitates respect for God and fellow human beings. Both fear and awe belong to what Otto calls the ‘numinous’, which is conceptualised in terms of pastoral care in this article.